PENGARUH KECEPATAN PUTARAN DAN WAKTU MESIN PENGUPAS PINANG TERHADAP KUALITAS HASIL PENGUPASAN - - Darmein; Ramli Usman (Jurnal Teknologi, 2016)
This research is aimed to gain  the appropriate turning rapidity to the quality of peeling product. It was focused on observing the capability of areca nut peeling machine to the speed and time of peeling. The research method was started from making the areca nut peeling machine and modifying the distance of cutting drum. The distance  or space of the cutting drum was varied in the same turning. The first rapidity  was arranged in 670 rpm , the guide drum in 1014 for the first peeling and 1627 for the second peeling. The result showed that the time of peeling process was 2kg/49 second.